Fatal Non-accidental Alpha-lipoic Acid Intoxication in an Adolescent Girl - Hadzik, B.; Grass, H.; Mayatepek, E.; Daldrup, T.; Hoehn, T. (Klinische Pädiatrie, 2014)
The aim of our report is to increase awareness that the antioxidant alpha-lipoic acid, which is marketed primarily as weight loss and energy supplement, has potentially lethal effects. A 14-year-old girl ingested in suicidal intention a large amount of alpha-lipoic acid, which led to multiorgan failure and subsequent death within 24 h. Multiorgan failure consisted of decreased myocardial contractility, seizures, anuria, thrombocytopenia, and coagulopathy. Therapy consisted of ventilation, anticonvulsive treatment and circulatory support with high-dose catecholamines. According to alpha-lipoic acid serum levels following ingestion the girl must have ingested a minimum of 10 alpha-lipoic acid tablets of 600 mg each. This is the first report on a fatal case of alpha-lipoic acid ingestion, which is intended to inform physicians, pharmacists and patients about critical side effects of this allegedly innocuous drug.
Keywords: alpha-lipoic acid; ingestion; multiorgan failure; suicide